Recurrent melanoma 25 years after initial diagnosis, presenting as metastatic disease early after heart transplantation - Gal Rubinstein; Benjamin Izar; Diana E. McDonnell; Andrea Fernandez Valledor; Justin A. Fried; Kevin Clerkin; Edward F. Lin; Dor Lotan; Farhana Latif; Gabriel Sayer; Nir Uriel; Jayant K. Raikhelkar (Cardio-Oncology)
Abstract Background Cancer survivors (CS) comprise a particularly high-risk group for both de-novo and recurrent malignancies after solid organ transplantation. Case presentation We report a case of relapsed melanoma, presented as metastatic disease seven months after heart transplantation in a patient who had an early-stage melanoma resected 25 years prior. Treatment with a combination of dabrafenib, a BRAF inhibitor, and trametinib, a mitogen-activated protein kinase (MEK) inhibitor resulted in a near-complete metabolic response, without major adverse effects. Conclusion This case demonstrates the increased risk of recurrence in CS with melanoma, which can persist decades after cancer diagnosis. These patients may be amenable to treatment using modern treatment modalities in oncology.